2006
DOI: 10.1590/s1413-86702006000600004
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection in non-hospitalized patients with cirrhosis and no symptoms of urinary tract infection: a case series study

Abstract: Bacterial infections are important factors in decompensation, and they increase the mortality rate of patients with liver cirrhosis. The most common infections among these patients are spontaneous bacterial peritonitis, pneumonia, skin infections and urinary tract infections (UTI). This transversal study evaluated the frequency of UTI in non-hospitalized patients with cirrhosis followed in a hepatology outpatient unit. Patients with clinical, laboratorial, echographic and/or histological diagnosis of cirrhosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…This inconsistency is supported by the report by Jansen et al, where PPIs were not found to be significantly associated with CHC clearance, opposite to our finding. However, similar findings have been reported for cirrhosis 48 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This inconsistency is supported by the report by Jansen et al, where PPIs were not found to be significantly associated with CHC clearance, opposite to our finding. However, similar findings have been reported for cirrhosis 48 …”
Section: Discussionsupporting
confidence: 90%
“…However, similar findings have been reported for cirrhosis. 48 Similar to the study by Ortiz et al, the exploration of DAAs in chronic renal disease remains challenging due to the excretion of some of these drugs by the kidneys, which may increase the potential for toxicities. 49 In a related condition, poor glycemic control and diabetes have been reported as negative predictors of CHC clearance and are associated with a higher risk of DAA failure.…”
Section: Discussionmentioning
confidence: 94%
“…Most notorious organisms responsible for UTI in this study were E. coli, Klebsiella and Pseudomonas in community acquired group. Cruz et al [38] also reported 5% UTI in cirrhotic patient with E. coli, Klebsiella. Fasolato et al [28] had shown urinary tract infections (46.2%) without ascites and (42.3%) with ascites.…”
Section: Discussionmentioning
confidence: 91%